2020
DOI: 10.1002/mco2.34
|View full text |Cite
|
Sign up to set email alerts
|

Effective antitumor activity of 5T4‐specific CAR‐T cells against ovarian cancer cells in vitro and xenotransplanted tumors in vivo

Abstract: Ovarian cancer is considered to be the most lethal gynecologic malignancy, and despite the development of conventional therapies and new therapeutic approaches, the patient's survival time remains short because of tumor recurrence and metastasis. Therefore, effective methods to control tumor progression are urgently needed. The oncofetal tumor‐associated antigen 5T4 (trophoblast glycoprotein, TPBG) represents an appealing target for adoptive T‐cell immunotherapy as it is highly expressed on the surface of vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Moreover, adoptive transfer of TPBG-CAR-T cells significantly delayed tumor formation in peritoneal and subcutaneous animal model xenografts. These results demonstrate the potential therapeutic effect and feasibility of immunotherapy with TPBG-CAR-T cells and provide a theoretical basis for future clinical trials of OC immunotherapy [ 34 ].…”
Section: Antigen Targetsmentioning
confidence: 86%
See 1 more Smart Citation
“…Moreover, adoptive transfer of TPBG-CAR-T cells significantly delayed tumor formation in peritoneal and subcutaneous animal model xenografts. These results demonstrate the potential therapeutic effect and feasibility of immunotherapy with TPBG-CAR-T cells and provide a theoretical basis for future clinical trials of OC immunotherapy [ 34 ].…”
Section: Antigen Targetsmentioning
confidence: 86%
“…TPBG is a potential target for adoptive T-cell immunotherapy because it is highly expressed on the surface of various tumor cells and has low expression in normal tissues. Guo et al [ 34 ] produced second-generation CAR-T cells specific for TPBG and showed that TPBG-CAR-T cells could induce lytic cytotoxicity and production of cytotoxic cytokines, including interferon gamma (IFNG), interleukin-2 (IL-2), and granulocyte-macrophage colony-stimulating factor. Moreover, adoptive transfer of TPBG-CAR-T cells significantly delayed tumor formation in peritoneal and subcutaneous animal model xenografts.…”
Section: Antigen Targetsmentioning
confidence: 99%
“…5T4 plays a role in tumor development and spread, and its expression correlates with poorer clinical outcomes. The selective tumor expression pattern of 5T4 together with its tumor-initiating and tumor-spreading role makes this molecule an attractive target for CAR T cell therapy ( 71 , 75 ).…”
Section: Generalities Of Ovarian Cancermentioning
confidence: 99%
“…Oncofetal TAA 5T4-targeted CAR T cell therapy was tested by Guo et al. ( 75 ). They developed second-generation human CAR T cells that showed specific concentration-dependent cytotoxicity against 5T4+ cells and significantly higher secretion of cytotoxic cytokines in vitro .…”
Section: Car T Cell Therapy In Ovarian Cancer and Peritoneal Carcinom...mentioning
confidence: 99%
“…Effective transduction of patient T cells with anti-5T4 CAR and antigen-specific secretion of IFN-γ was produced by the co-culture of CAR-T cells and matched autologous tumor catabolites. And IFN-γ production correlated with tumor cell surface 5T4 expression levels ( 122 , 123 ). In addition, CAR-T therapy modulated the differentiation of T cells through IFN-γ affecting tumor immunity ( 124 ).…”
Section: The Roles Of Interferons In Oc Treatmentmentioning
confidence: 99%